Myeloid GPSM1 regulates atherosclerosis progression by governing monocyte and macrophage activation and chemotaxis - Yuemei Zhang; Yuxin Cao; Yongxin Sun; Chenxia Zhou; Xiaorui Lyu; Daixi Wang; Jiangfei Zheng; Yuxin Shu; Lijun Yao; Rong Zhang; Jingyong Li; Feng Jiang; et al. (Proceedings of the National Academy of Sciences, 2025)
The activation of blood monocytes and the infiltration of monocyte-derived macrophages into the vessel walls are the central part of atherosclerosis. However, the mechanisms underlying the processes remain unclear. Here, we report that G-protein signaling modulator 1 (GPSM1) plays a critical role in atherogenesis. We found that GPSM1 expression in lesional macrophages was increased during atherosclerosis development both in mice and humans. Myeloid-specific GPSM1 ablation protects mice against atherosclerosis and reduces aortic inflammation in both Apoe −/− mice and an AAV-PCSK9 injection model. Conversely, myeloid-restricted overexpression of GPSM1 accelerates aortic inflammation and promotes atherosclerosis development in mice. Mechanistically, GPSM1 deficiency suppressed monocyte activation including chemotaxis and adhesion through inhibition of the p38/ERK MAPK pathway regulated by the cAMP/PKA/KLF4/PMP22 axis, thereby alleviating proinflammatory responses within atherosclerotic plaques. Blockade of PMP22 using siRNA-loaded liposomes protected GPSM1 overexpression mice from atherosclerosis. Furthermore, a small-molecule compound inhibiting GPSM1 function could suppress atherosclerosis in vivo. In conclusion, our findings establish that GPSM1 is a regulator of atherosclerosis development and targeting GPSM1 might be a promising therapy against atherosclerosis.